Mediating Role of Knowledge Sharing Between Transformational Leadership and Innovative Service Delivery Among Nurses in the Federal Medical Centers of North East Nigeria - Oki, Emmanuel Umoru; Maimako, Seddi Sabestian; Abba, Tijjani (PT FORMOSA CENDEKIA GLOBAL, 2024)
In a style of a quantitative research, the study examines the mediating role of knowledge sharing between transformational leadership and innovative service delivery of health workers (nurses) in the federal medical centers within northeastern Nigeria. The research methodology applied a descriptive survey and a cross sectional study using structured questionnaires. The population of the study was 3200 nurses of the federal medical center of the north east Nigeria and the sample size was 534. Data were analyzed using Smart-PLS 4.0. The findings of the study shows that transformational leadership strongly influences innovative service delivery (β =0.328, t=4.218, p=0.000), Knowledge sharing is impacted by transformational leadership (β=0.760, t=31.062, p=0.000), Knowledge Sharing significantly affects Innovative service Delivery. (β=0.527, t=6.873, p=0.000), Knowledge sharing strongly influences the link between Transformational Leadership and Innovative service Delivery (β=0.400, t=6.454, p=0.000). The study recommends that further studies should take into consideration other sectors of the economy, such as the manufacturing, technological and educational sector. Again, a longitudinal study should be carried out and other regions in the country should be studied to compare results